Evaluation of the Pharmacokinetic Interaction Between the Voltage‐ and Use‐Dependent Nav1.7 Channel Blocker Vixotrigine and Carbamazepine in Healthy Volunteers. Issue 1 (24th October 2019) - Dunbar, Joi; Versavel, Mark; Zhao, Yuan; Tate, Simon; Morisset, Valerie; Giblin, Gerard M. P.; Palmer, Joanne; Tidemann‐Miller, Beth; Naik, Himanshu
Abstract: Vixotrigine is a voltage‐ and use‐dependent Nav1.7 channel blocker under investigation for the treatment of peripheral neuropathic pain conditions, including trigeminal neuralgia. Vixotrigine is metabolized primarily via uridine diphosphate‐glucuronosyltransferases (UGTs). Carbamazepine, a UGT and cytochrome P450 3A4 inducer, is a first‐line treatment for trigeminal neuralgia. We conducted a double‐blind, randomized, placebo‐controlled, parallel‐group, single‐center phase 1 study to investigate the impact of coadministering vixotrigine and carbamazepine on their respective pharmacokinetics (PK) in healthy volunteers, the safety and tolerability of combined treatment, and PK recovery of vixotrigine following carbamazepine discontinuation. Randomly assigned treatments were carbamazepine (100 mg twice a day, days 1‐3 and 200 mg twice a day, days 4‐21) or placebo on days 1 to 21. All volunteers received vixotrigine 150 mg 3 times a day on days 16 to 28. At prespecified times, whole‐blood samples were collected for PK assessment. Statistical analyses were performed on the log‐transformed PK parameters area under the concentration‐time curve within a dosing interval (AUC0‐tau ) and maximum observed concentration (Cmax ) for vixotrigine, carbamazepine, and metabolites. Vixotrigine AUC0‐tau and Cmax were reduced by 31.6% and 26.3%, respectively, when coadministered with carbamazepine compared with placebo. Seven days after carbamazepine discontinuation, vixotrigine AUC0‐tau and Cmax remained 24.5% and 21.4% lower compared with placebo. Carbamazepine AUC0‐tau and Cmax were <10% lower when coadministered with vixotrigine compared on days 15 and 21. Vixotrigine/carbamazepine coadministration was well tolerated. These results suggest that vixotrigine does not have an effect on carbamazepine PK, and although carbamazepine has an effect on the exposure of vixotrigine, the effect is not considered clinically relevant.